2011
DOI: 10.1007/s10979-010-9223-7
|View full text |Cite
|
Sign up to set email alerts
|

Correctional policy for offenders with mental illness: Creating a new paradigm for recidivism reduction.

Abstract: Offenders with mental illness have attracted substantial attention over the recent years, given their prevalence and poor outcomes. A number of interventions have been developed for this population (e.g., mental health courts). They share an emphasis on one dimension as the source of the problem: mental illness. Their focus on psychiatric services may poorly match the policy goal of reducing recidivism. In this article, we use research to evaluate (a) the effectiveness of current interventions, and(b) the larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
331
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 343 publications
(352 citation statements)
references
References 82 publications
18
331
2
1
Order By: Relevance
“…Broad-based benefits like these might be expected to reduce arrests. On the other hand, most mental health interventions aim to reduce symptoms and associated impairments and do not directly target factors leading to arrests of people with mental illnesses (6). Also, outpatient commitment involves heightened surveillance that could elevate the chance of being apprehended.…”
mentioning
confidence: 99%
“…Broad-based benefits like these might be expected to reduce arrests. On the other hand, most mental health interventions aim to reduce symptoms and associated impairments and do not directly target factors leading to arrests of people with mental illnesses (6). Also, outpatient commitment involves heightened surveillance that could elevate the chance of being apprehended.…”
mentioning
confidence: 99%
“…However, the effectiveness of first-generation interventions is questionable. Skeem et al (2011) reviewed studies of first-generation interventions and found no relationship between reduced recidivism and reduced symptoms of SMI. Incarnations of the MHCs vary depending on local laws, resources, institutions, populations and so on.…”
Section: A U T H O R C O P Ymentioning
confidence: 99%
“…And it is somewhat out of keeping with the more nuanced literature on the relationship between violence and mental disorder. Clearly, there are individual cases where the link is undisputed; but the literature is more hesitant about the generality of the link (Peterson et al 2014;Skeem et al 2011). And Buchanan and Zonana (2009) argue powerfully that psychiatrists ought only to offer possibility explanations to the courts about unusual event and reserve explanatory assertions for more routine or mundane events.…”
Section: Partial Culpability and Causation In R V Clarencementioning
confidence: 99%